Students' views on the block evaluation process: A descriptive analysis - Ntefeleng E. Pakkies; Ntombifikile G. Mtshali (AOSIS, 2016)
Background: Higher education institutions have executed policies and practices intended to determine and promote good teaching. Students' evaluation of the teaching and learning process is seen as one measure of evaluating quality and effectiveness of instruction and courses. Policies and procedures guiding this process are discernible in universities, but it isoften not the case for nursing colleges. Objective: To analyse and describe the views of nursing students on block evaluation, and how feedback obtained from this process was managed.Method: A quantitative descriptive study was conducted amongst nursing students (n = 177) in their second to fourth year of training from one nursing college in KwaZulu-Natal. A questionnaire was administered by the researcher and data were analysed using the Statistical Package of Social Sciences Version 19.0. Results: The response rate was 145 (81.9%). The participants perceived the aim of block evaluation as improving the quality of teaching and enhancing their experiences as students.They questioned the significance of their input as stakeholders given that they had never been consulted about the development or review of the evaluation tool, or the administration process; and they often did not receive feedback from the evaluation they participated in. Conclusion: The college management should develop a clear organisational structure with supporting policies and operational guidelines for administering the evaluation process. The administration, implementation procedures, reporting of results and follow-up mechanisms should be made transparent and communicated to all concerned. Reports and actions related to these evaluations should provide feedback into relevant courses or programmes. Keywords: Student evaluation of teaching; perceptions; undergraduate nursing students; evaluation process